Value for money : budget and financial management reform in the People's Republic of China, Taiwan and Australia - Podger, A. S. (Andrew S.); Su, Tsai-Tsu; Wanna, John; Chan, Hon S.; Niu, Meili (ANZSOG (Series), 2018)
The Greater China Australia Dialogue on Public Administration has held annual workshops since 2011 on public administration themes of common interest to the People's Republic of China, Taiwan and Australia. This book presents and discusses a selection of papers developed from the Dialogue's fifth workshop held in late 2015 hosted by the National Taiwan University in Taipei. The theme, 'Value for Money', focused on budget and financial management reforms, including how different nations account for the relative performance of their public sectors. All governments face the challenge of scarce resources requiring budgetary management processes for identifying the resources required by and available to government, and then for allocating them and ensuring their use or deployment represents value for money. Such budgetary and financial management processes need to inform decision-making routinely and protect the integrity of the way public resources are used - with some public accountability to indicate that their uses are properly authorised and reflect the policies of legitimate government leaders. The chapters in this book explore budgeting and financial management in three very different jurisdictions: Australia, the People's Republic of China and the Republic of China (Taiwan). These activist and at times innovative countries are keen to analyse and reflect upon each other's policy achievements and patterns of public provision. They are keen to learn more about each other as their economic and social engagement continues to deepen. They are also conscious that fundamental differences exist in terms of economic development and global strategic positioning, and levels and philosophies of political development; to an extent these differences are representative of differences amongst countries around the globe.